(3QSGdI LhGH Ydi SDGd Peis - (3CHh GdhaG YdGA GdOjf Hf YWjI Hf MSf, GdTjN YdhGfs ((3YHO GdhgGH Hf SdjeGf Hf YHO GdhgGH GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje deG cGf HJGQjN TgQ QHYj GdKGfi ef TghQ SfI SHY YTQI hJSYeGFI hQO SDGd ef MeU Ydi dSGf QLd Pei fXekG Edi SjOfG CHh GdhaG YdGA GdOjf s
(3BNQgG (B:s
(3hMSHi ef GdCchGf QHi Efg SejY bQjH hGdeLjH dOYhI hdG Mhd EdG HGddg hdG bhi Hg CQJLi dWakG jbjd dYKQI Je GdLhGH HYhf Gddg hbhJg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3efXheIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , LeYjI GdebGUO GdESdGejI (B- (3eYgO GdOQGSGJ GdESdGejI (B((3Yde GdcdGe (B4/89) s
Keywords: (3Gdabg GdESdGejs